Management of epilepsy in elderly (Medical Journal of Indonesia, 2003)
Management of epilepsy in elderly requires understanding the unique biochemical and pharmacological characteristics of these patients. Management decisions must be based on accurate classification of seizures or epilepsy syndromes, a thorough neurological assessment to define etiology, and a comprehensive assessment of the patient’s health and living situation. Concomitant illnesses such as neurological, psychiatric, metabolic, or cardiac disorders will require individualization of plans and instructions. Specific problems of treatment of epilepsy in the elderly compared to childhood patients are as follows: distinctive range of causes of epilepsy, distinctive differential diagnosis, concurrent pathologies unrelated to epilepsy, pharmacokinetic and pharmacodynamic differences, and distinctive psychosocial effects. (Med J Indones 2003; 12: 40-7) Keywords: epilepsy, elderly, management, concomitant illness, pharmacokinetic